Different Interests Explain Different Proposals: The Contestation of Indo-Pacific Cooperation Framework between ASEAN and the US - Sri Yunanto; Galby Rifqi Samhudi (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2019)
The rise of China that goes along with strategic shifts around the Indian and the Pacific Ocean has started a new stage of major power contestation recently. ASEAN which acts as a host in Southeast Asia has certain stands to deal with the challenges and opportunities presented by the competition. On the other hand, the US Government with its global interests will never ever allow this region to fall into China’s influence. Simultaneously, both ASEAN and the US have the same approach in this situation to utilize the framework of Indo-Pacific cooperation that is definitively open to any explication in order to gain advantages resulted from the global interaction over the region. Nevertheless, their perceptions on the matter of defining the cooperative framework of Indo-Pacific are apparently diverse. Hence, this paper attempts to analyze the rationale of ASEAN and the US development of the Indo-Pacific cooperative concept based on their respective strategic assessment. This paper argues that the distinctive interests and insight of threats from ASEAN and the US toward the rise of China as well as major power contestation in the region are being the two main factors in their different perceptions on the concept of Indo-Pacific cooperative framework.